Atrial fibrillation in patients with an atrial septal defect in a single centre cohort during a long clinical follow-up: its association with closure and outcome of therapy. Issue 2 (17th August 2020) - Evertz, Reinder; Reinders, Manon; Houck, Charlotte; ten Cate, Tim; Duijnhouwer, Anthonie L.; Beukema, Rypko; Westra, Sjoerd; Vernooy, Kevin; de Groot, Natasja M S
Abstract : Objective: Currently, consensus is lacking on the relation between closure of atrial septal defect (ASD) and the incidence of atrial fibrillation (AF), which is a known complication in ASD patients. More importantly, studies reporting on the treatment applied for AF in ASD patients are scarce. The aims of this study were (1) to assess the incidence of AF in ASD patients, (2) to study the relation between closure and AF and (3) to evaluate applied treatment strategies. Methods: A single-centre retrospective study in 173 patients with an ASD was performed. We analysed the incidence of AF, the relation of AF with closure, method of closure and the treatment success of therapies applied. Results: Almost 20% of patients with an ASD developed AF, with a mean age of 59 (±14) years at first presentation of AF during a median clinical follow-up of 43 (29–59) years. Older age (OR 1.072; p<0.001) and a dilated left atrium (OR 3.727; p=0.009) were independently associated with new-onset AF. Closure itself was not independently associated with AF. First applied treatment strategy was rhythm control in 77%. Of the 18 patients treated with antiarrhythmic drugs 50% had at least 1 recurrence of AF. Conclusion: No clear relation between closure of the ASD and AF could be assessed. This is the first study describing applied therapy for AF in ASD patients of which medical rhythm control was the most applied strategy with a disappointing efficacy.